The effects of oral antidiabetic drug metformin on liver metabolism by real-time cell monitoring system - (:unkn) unknown (MEDIMOND S R L, 2016)
Introduction: Non-alcoholic fatty liver disease is associated with like other insulin resistance syndromes with obesity, hypertriglyceridemia, diabetes and hypertension metformin is known to restrict hepatic gluconeogenesis and reduces glycogenolysis. Objectives: The study was investigated for the proliferative capacity of AML12 hepatocytes by continuous monitoring assay (iCELLigence system) to investigate cytotoxicity of oral antidiabetic drug metformin. The effects of metformin on gene expression profiles of FTO, CD68 and RAN in AML12 hepatocytes were also evaluated. Methods: iCELLigence cell index (CI) impedance measurements were performed in AML12 hepatocyte cell line after resuspended in medium and adjusted to subsequently 100.000 cells/mL. After seeding 150 mu L of the cell suspensions into the wells of the E-plate L8, AML12 cells were monitored every 15 min for a period of up to 96h by the iCELLigence system. Gene expression profiles were determined with qPCR Results: Half maximum inhibitory concentrations (IC50) were determined based on the dose-response curves derived by iCELLigence measurements. IC50 values for 24h metformin exposed AML12 hepatocytes were 230 mu M after 24h metformin administration which demonstrate the therapeutic affect of metformin at 230 mu M concentration after 24h is prominent in hepatocytes. Metformin administred decreasing effect over FTO, CD68, and RAN gene expressions compared to control hepatocytes. Conclusion: In conclusion, 230 mu M metformin therapy may be effective in improving glucose homeostasis via changing the gene expression of RAN, these pathways may have therapeutic results and supply the new strategies for treatment of insulin resistance.
Keywords: AML12 hepatocyte; iCELLigence system; metformin; non-alcholic fatty liver disease; WHITE ADIPOSE-TISSUE; FTO GENE; OBESITY; INFLAMMATION; LIPOTOXICITY; ASSOCIATION; HOMEOSTASIS; CHILDHOOD; STRESS; RAN